Leser-Trélat sign as a rare manifestation of cutaneous melanoma - Niccolò Gori; Ilaria Esposito; Laura Del Regno; Alessandra D'Amore; Ketty Peris; Alessandro Di Stefani (PAGEPress Publications, 2020)
Leser-Trélat Sign (LTS) is a rare paraneoplastic syndrome characterized by the sudden eruption of multiple seborrheic keratoses in patients with internal malignancy, commonly localized in the gastrointestinal tract. We report an 80-year-old female patient showing a rapid increase in the number and size of seborrheic keratosis associated with the diagnosis of a cutaneous nodular melanoma (Breslow thickness: 4.5 mm) located on the right flank. After the excision of melanoma, subsequent staging procedures resulted negative, moreover no evidence of melanoma recurrence and no changes of the seborrheic keratoses was detected after a follow-up of 52 months. Although the association between melanoma and Leser Trelat sign is rare, an accurate skin examination with the aid of dermatoscopy searching for undiagnosed skin cancers, should be suggested in patient with sudden eruption of keratosis seborrheic to early diagnose and treat a possible melanoma.